Compound heterozygote KCNQ1 mutation causing Jervell Lange Neilson syndrome: a case report of genotype-phenotype correlation - Agarwal, Khushboo; Shankar, Guruprasad H.; Sarangi, Bhakti; Walimbe, Ajay (International Journal of Contemporary Pediatrics, 2021)
Congenital sensorineural hearing loss (SNHL) is a common phenomenon with several genetic and non-genetic associations that require early diagnosis and work-up to prompt appropriate interventions. Of the genetic associations, Jervell and Lange-Nielsen syndrome (JLNS) remains a rare monogenic disease that is characterized by SNHL, prolongation of QT interval, syncopal attacks due to ventricular arrhythmias and sudden cardiac death from very early in life. We hereby report a 5 years old girl with SNHL and recurrent blackout episodes in early childhood with significant family history, admitted for cochlear implant who developed ventricular arrhythmias requiring multiple interventions with further investigations revealing a prolonged QT interval on electrocardiography (ECG) with metabolic abnormalities (hypomagnesemia and hypokalemia). Her clinical exome study showed a compound heterozygous KCNQ1 mutation, a more sporadic form of JLNS managed using oral beta-blocker. This experience illustrates the relevance of a detailed systemic evaluation with an elaborate cardiac assessment in children with SNHL, more so in the presence of frequent unexplained acute life-threatening episodes.